ANALISIS PREDIKSI KEBANGKRUTAN DENGAN MENGGUNAKAN METODE ALTMAN Z-SCORE PADA PT.ADHI KARYA (PERSERO) TBK - Novien Rialdy (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
ABSTRACTThis research aims to predict, analyze and determine the level of potential bankruptcy of a company using Altman Z-Score method at PT.Adhi Karya Tbk period 2012 until 2016. This research also aims to improve the company's financial petformance based on discriminant analysis results with using Altman model. Discriminant analysis was done to predict the bankruptcy of a company by analyzing the financial statements of a company up to five years. This research used descriptive approach. Data type that used was quantitative data. The data sources that used in this research were the secondary data. Data collection technique was a documentation technique. Data analysis technique in this research was descriptive analysis techniques.The results showed that in the first 3 years, the company was in a state of gray bankruptcy (gray area), whereas in the last 2 years the company in the category of potentially bankrupt. It caused because the value of Z-Score produced by the company fluctuated from year to year, Z-Score values produced every year were below the standards of a company that said to have good financial petformance. The decline in the value of Z-Score was caused by several factors such as decreased corporate earnings, higher corporate debt levels and working capital generated by companies that did not stable evely year.Keywords: Bankruptcy Analysis, Altman Z-Score Method